PENGARUH EKUITAS MEREK TERHADAP REPURCHASE INTENTION HANDPHONE MEREK SAMSUNG KEPADA MAHASISWA FAKULTAS EKONOMI UNIVERISTAS TADULAKO DI KOTA PALU - NURSYAMSU, SYARIFUDDIN (Fakultas Ekonomi Universitas Tadulako, 2015)
This study aims to determine how much the brand equity effect to repurchase intention Samsung brand mobile phone to the students of the faculty of economics Tadulako University, Palu. The research method used is descriptive of causal method with a sample of 75 people with non-probability sampling technique with a purposive sampling approach and Multiple Linear Regression Analysis method with the aid of a computer program SPSS for Windows Release 16.0. The results showed that: 1). brand equity consists of brand awareness, perceived quality, brand association and brand loyalty simultaneously affect significantly on repurchase intention Samsung brand mobile phone to the students of the faculty of economics Tadulako University, Palu; 2). Brand awareness partially have no significant effect on repurchase intention Samsung brand mobile phone to the students of the faculty of economics Tadulako in Palu; 3). Perceived quality, brand association, and brand loyalty is partially affect significantly on repurchase intention Samsung brand mobile phone to the students of the faculty of economics Tadulako in Palu.